Proses Pembelajaran Berdasarkan Ulangan 6:6-9 - Olivia Lili (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2021)
There are so many learning processes in implementing education today. As Christians, we have a basic truth in doing various things, including the implementation of education. Many texts in the Bible talk about educating children. In the book of Deuteronomy 6: 6-9 is found God's commandment to parents/adults to educate children. The text in Deuteronomy 6: 6-9 is generally only understood as a command to carry out education about God in the family, but the author views the text in Deuteronomy 6: 6-9 also shows a learning process that can be developed to help children understand the eyes. lessons at school. The author will analyze the text of Deuteronomy 6: 6-9 to find the existing learning process, with the aim of helping teachers and parents accompany the teaching and learning process according to the truth of God's Word.